Learning Food Security from Original Tribe in Borneo - Muhammad Azmi, Siti Marfuah & Heri Susanto (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
Food security is a very important factor in the development of humankind fromantiquity to modern times. Along with the increasing world population, the need forfood is increasing. Insufficient food can have a positive impact in various sectors,particularly the political, economic and health of a country. Increasing the number ofresidents not accompanied by the addition of agricultural land will certainly have animpact on the lack of world food supplies. Lack of food raw materials will affect theincrease in the number of hungry. Famine will have an impact on the political andeconomic stability of a country. Not to mention other hazards that could arise because ofhunger, such as rising crime and declining levels of public education. This paperdiscusses the overview of local knowledge from the Dayak Tribe in Kalimantan tofostering food security.Keywords: food security, Dayak tribe, Borneo